Genetic and Physiological Characterization of Two Clusters of Quantitative Trait Loci Associated With Seed Dormancy and Plant Height in Rice - Ye, Heng (Genetics Society of America, 2013)
Seed dormancy and plant height have been well-studied in plant genetics, but their relatedness and shared regulatory mechanisms in natural variants remain unclear. The introgression of chromosomal segments from weedy into cultivated rice (Oryza sativa) prompted the detection of two clusters (qSD1-2/qPH1 and qSD7-2/qPH7) of quantitative trait loci both associated with seed dormancy and plant height. Together, these two clusters accounted for >96% of the variances for plant height and ~71% of the variances for germination rate in an isogenic background across two environments. On the initial introgression segments, qSD1-2/qPH1 was dissected genetically from OsVp1 for vivipary and qSD7-2/qPH7 separated from Sdr4 for seed dormancy. The narrowed qSD1-2/qPH1 region encompasses the semidwarf1 (sd1) locus for gibberellin (GA) biosynthesis. The qSD1-2/qPH1 allele from the cultivar reduced germination and stem elongation and the mutant effects were recovered by exogenous GA, suggesting that sd1 is a candidate gene of the cluster. In contrast, the effect-reducing allele at qSD7-2/qPH7 was derived from the weedy line; this allele was GA-insensitive and blocked GA responses of qSD1-2/qPH1, including the transcription of a GA-inducible α-amylase gene in imbibed endosperm, suggesting that qSD7-2/qPH7 may work downstream from qSD1-2/qPH1 in GA signaling. Thus, this research established the seed dormancy-plant height association that is likely mediated by GA biosynthesis and signaling pathways in natural populations. The detected association contributed to weed mimicry for the plant stature in the agro-ecosystem dominated by semidwarf cultivars and revealed the potential benefit of semidwarf genes in resistance to preharvest sprouting.